Evidence for oxidation at the base of the nakhlite pile by reduction of sulfate salts at the time of lava emplacement. (15th October 2018) - Dottin, James W.; Labidi, Jabrane; Farquhar, James; Piccoli, Philip; Liu, Ming-Chang; McKeegan, Kevin D.
Abstract: The assimilation of sulfate by Martian melts could explain the highly oxidized state of some Martian nakhlite meteorites, such as those paired with MIL 03346 (MIL 090030, MIL 090032, and MIL 090136). Here, a combination of new sulfur isotope data, mineral composition and abundance data, and consideration of mineral textures is used to link assimilation of surface-derived Martian sulfate to oxidation of nakhlite melts. The magnitudes of the mass independent sulfur isotope signatures (negative Δ 33 S) and the abundance of sulfide minerals accounts for much of the added oxygen implied by the occurrence of abundant skeletal titanomagnetite in the MIL pairs. Assimilation and reduction of sulfate amounts equivalent to that from 10′s of centimeters of Martian sediment are required to account for an oxidation front extending ∼1 m into the flow, a position previously proposed for MIL 03346, and implies a position at the bottom, rather than the top of a nakhlite flow. A similar positional and amount constraint is required for an alternative path for assimilation of sulfate from sulfate-rich brine. Assimilation and reduction of sulfate is therefore inferred to play a critical role in establishing both the enrichment in skeletal titanomagnetite within the lower portion of the nakhlite pile and the large Δ 33 S anomalies of the MIL pairs. Other nakhlites with smaller Δ 33 S anomalies and less titanomagnetite would occupy positions farther away from the source of sulfate.